2021
DOI: 10.3390/ijerph18116010
|View full text |Cite
|
Sign up to set email alerts
|

Age-Graded Transitions and Turning Points in Polish Offenders’ Criminal Careers from the Standpoint of Life Course Theory

Abstract: Both juvenile and adult criminal careers show regularities in the origins of delinquency, the dynamics of the criminal pathway, and the turning points that lead to desistance/persistence in crime. Research shows that family, education, and friendship environments contribute significantly to the individual choices that create criminal biographies. Our aim was to apply core aspects of life course theory (LCT): trajectory, the aged-graded process, transitions, institutions, and ultimately how desistance/persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Because we carried out these interviews in correctional facilities, authorities did not permit us to use recording equipment. Following others, we employed an open-ended biographical-focused questionnaire that was subject-driven (Chomczyński 2018;Fleetwood 2015;Noaks and Wincup 2004;Pękala et al 2021aPękala et al , 2021bSilverman 2011). Some interviews were prearranged while others occurred by a chance meeting and discussion with a dealer that we encountered in our fieldwork.…”
Section: Research Setting and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we carried out these interviews in correctional facilities, authorities did not permit us to use recording equipment. Following others, we employed an open-ended biographical-focused questionnaire that was subject-driven (Chomczyński 2018;Fleetwood 2015;Noaks and Wincup 2004;Pękala et al 2021aPękala et al , 2021bSilverman 2011). Some interviews were prearranged while others occurred by a chance meeting and discussion with a dealer that we encountered in our fieldwork.…”
Section: Research Setting and Methodsmentioning
confidence: 99%
“…Ricardo, a dealer, received training from peers and older adults. In informal discussions, lowprofile dealers revealed that their entry began by observing those more experienced at the trade through learning and imitation (Akers et al 1979;Pękala et al 2021aPękala et al , 2021bTarde 1962). The main difference in our findings and those cited above is our subjects' unwillingness to acknowledge their activity as deviant (Becker 1963).…”
Section: Entering the Trade Of Cannabis Dealingmentioning
confidence: 99%